Analisis Faktor Konfirmatori Persepsi Mahasiswa Terhadap Kualitas Pelayanan Pendidikan Confirmatory Factor Analysis of Student Perceptions of the Quality of Education Services - Subandi Subandi (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2023)
Quality of service is very important for the sustainability of higher education. The purpose of this study is to identify indicators forming the quality of service. The sample used was 150 students. Data analysis technique using Second Order CFA. The results of the CFA analysis of the Relationship dimension have the highest value. For indicators that form service quality, the highest value is the Internationalization indicator.